A Metal–Polyphenol Network Coated Nanotheranostic System for Metastatic Tumor Treatments. Issue 48 (10th November 2017) - Fan, Jin‐Xuan; Zheng, Di‐Wei; Mei, Wen‐Wen; Chen, Si; Chen, Si‐Yi; Cheng, Si‐Xue; Zhang, Xian‐Zheng
Abstract: As a characteristic trait of most tumor types, metastasis is the major cause of the death of patients. In this study, a photothermal agent based on gold nanorod is coated with metal (Gd 3+ )‐organic (polyphenol) network to realize combination therapy for metastatic tumors. This nanotheranostic system significantly enhances antitumor therapeutic effects in vitro and in vivo with the combination of photothermal therapy (PTT) and chemotherapy, also can remarkably prevent the invasion and metastasis due to the presence of polyphenol. After the treatment, an 81% decrease in primary tumor volumes and a 58% decrease in lung metastasis are observed. In addition, the good performance in magnetic resonance imaging, computerized tomography, and photothermal imaging of the nanotheranostic system can realize image‐guided therapy. The multifunctional nanotheranostic system will find a great potential in diagnosis and treatment integration in tumor treatments, and broaden the applications of PTT treatment. Abstract : A metal–polyphenol network coated nanotheranostic system for metastatic tumor treatments is developed. The theranostic system can inhibit primary tumor and suppress tumor metastasis effectively with combined photothermal and chemotherapy and the release of polyphenol. Moreover, the system shows superior imaging capability in computerized tomography and magnetic resonance imaging.